Acquisition of Sentence Patterns in Children at the Telegraphic Stage - Siska Dwi Cahyani; Rahayu Pujiastuti (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2025)
This research aims to describe children's sentence pattern acquisition at the telegraphic stage. This research is a case study. The data in this research is in the form of utterances that can inform children's sentence patterns at the telegraphic stage. The data source is a child who is 2;3 years old and uses Indonesian as his first language. Data collection in this study used the techniques of listening, fishing, recording, and noting. The data analysis procedure in this study, re-examining the collected data, classifying, coding, interpreting, and concluding. The results of this study provide information about the acquisition of sentence patterns in children at the telegraphic stage, sentence patterns consisting of (1) one function, including subject function (S), predicate function (P), object function (O), and adverbial function (K); (2) two functions, including S-P, P-S, and P-O sentence patterns; (3) three functions, including S-P-O and S-P-K sentence patterns. The development of children's sentence patterns at the telegraphic stage illustrates their cognitive development so that it is useful for PAUD teachers to choose teaching materials and learning media that facilitate children's language development.